Penggunaan Kelambu Berinsektisida Terhadap Pencegahan Malaria di Kota Jayapura - Oktliana Pasangka; Elisabet Bre Boli (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
The content of the abstract, between 150-200 words, just one paragraph. Apparently, for the sake of simplicity, use the same language you use in your writing. Use the Abstract Fill style for this format. If you use this template correctly, all numbering will be generated automatically. So you don't need to edit it manually. Of course, if you create a section of this paper that requires numbering after this template, that number will be followed by the existing section number. Again you don't need to edit the part numbers, because if the contents of this template are deleted, the numbers will be sorted automatically. If you want to try deleting the contents of this template, please backup it first.